Integration of Pianica Application as Interactive Media in Learning National Songs in Grade IV Elementary School - Rahmadhani, Renita Mila; Sa’diyah, Halimatus; Wijayanto, Wasis (Jurnal Prajaiswara, 2025)
Introduction/Main Objectives: This study aims to characterize how well a digital pianica application, when integrated as an interactive learning tool, can improve learning interest, understanding of number notation, and the ability to play the national song "Ibu Kita Kartini" in fourth grade elementary school. Research Methods: Descriptive qualitative methodology was used, and data were collected through documentation, interviews, and observations. Finding/Results: According to the study findings, the use of the pianica program can increase students' enthusiasm, make it easier for them to understand number notation, and inspire their courage and overall musical ability. The program makes learning fun and efficient by offering customizable activities along with attractive visual and audio displays. Conclusion: These results highlight the value of using digital media as an alternative to traditional methods of teaching music in elementary schools.